Clinical features and outcome of prosthetic pulmonary valve infective endocarditis - Pastor, Daniel; Castillo, Juan Carlos; González, Rafael; González, Rafael; López-Aguilera, José; Mesa, Dolores; Anguita, Manuel; Anguita, Manuel; Pan, Manuel (Journal of Cardiovascular Medicine and Cardiology, 2022)
Background: Infective endocarditis is a serious complication in patients with prostheses in the right ventricle outflow tract. The aim of our study is to assess clinical features in these patients. Methods: We have analyzed all cases of prosthetic pulmonary valve infective endocarditis (PPVIE) and compared them to the rest of the patients with IE. Since the year 2000, 375 cases of IE have been diagnosed in our center and nine patients had a PPVIE.: 3 patients with Melody percutaneous prostheses, 5 with a homograft (3 after a Rastelli procedure, 2 a Ross procedure), and 1 patient with a heterograft (Contegra conduit). Results: Mean age of PPVIE patients was 31±15 years old and 89% were male. A presumed portal of entry could only be identified in 4 of the 9 patients with PPVIE. The most common was a dental origin (3 patients). A causative microorganism was detected in all but one PPVIE patient: 3 S.viridans, 2 S.aureus, 2 coagulase-negative staphylococci, and 1 enterococcus. Most patients suffered complications during the in-hospital phase: 7 out of 9 PPVIE patients (78 vs.75% of the rest of IE patients), the most common congestive heart failure (5 patients), and persistent sepsis (4 patients). Six patients were operated on during hospitalization (67 vs. 55%) with a mean time from admission to surgery of 15 days. In-hospital mortality was similar (22 vs. 26%). Conclusions: Prevalence of PPVIE is low, with a clinical outcome, surgery rate, and survival similar to the rest of patients with IE.